"ROLE AND IMPACT OF SOCIAL MEDIA IN 2014 GENERAL ELECTIONS WITH SPECIAL REFERENCE TO PUNJAB” - Rambani, Vishal (Innovative Research Thoughts, 2018)
Digital media is the best approach for political parties to reach a worldwide audience in today's times of expanding social media usage and greater internet penetration, thanks to the proliferation of smartphones and the saturation of traditional media.It is now easier than ever to target specific groups of people and tailor campaigns to their preferences thanks to the wide reach of digital and social media platforms. This was India's first election in which social media was used by 1.2 billion people, and it was during the Lok Sabha elections of 2014. As far as political campaign promotion goes, India's marketing and PR sector is dominated by social media. A whole new battlefield has opened up in the war for attention. India's next Prime Minister, Narendra Modi, is widely expected to replace Barack Obama. With the use of hedging methods, politicians benefited from this election's results. The power of social media allowed to reach out to voters in ways that were previously unimaginable. This paper describes an overview of impact of social media on politics with history of Political Process in Punjab and Parliamentary Elections 2014 in Punjab. A survey was used in this paper. 390 social media users selected from Punjab of age group 18 to 46 years. Data analysed by SPSS.